Analysis and cloning of the synthetic pathway of the phytohormone indole-3-acetic acid in the plant-beneficial Bacillus amyloliquefaciens SQR9 - Shao, Jiahui; Li, Shuqing; Zhang, Nan; Cui, Xiaoshuang; Zhou, Xuan; Zhang, Guishan; Shen, Qirong; Zhang, Ruifu (Microbial cell factories, 2015)
The plant growth-promoting rhizobacteria (PGPR) strain Bacillus amyloliquefaciens SQR9, isolated from the cucumber rhizosphere, protects the host plant from pathogen invasion and promotes plant growth through efficient root colonization. The phytohormone indole-3-acetic acid (IAA) has been suggested to contribute to the plant-growth-promoting effect of Bacillus strains. The possible IAA synthetic pathways in B. amyloliquefaciens SQR9 were investigated in this study, using a combination of chemical and genetic analysis. Gene candidates involved in tryptophan-dependent IAA synthesis were identified through tryptophan response transcriptional analysis, and inactivation of genes ysnE, dhaS, yclC, and yhcX in SQR9 led to 86, 77, 55, and 24 % reductions of the IAA production, respectively. The genes patB (encoding a conserved hypothetical protein predicted to be an aminotransferase), yclC (encoding a UbiD family decarboxylase), and dhaS (encoding indole 3-acetaldehyde dehydrogenase), which were proposed to constitute the indole-3-pyruvic acid (IPyA) pathway for IAA biosynthesis, were separately expressed in SQR9 or co-expressed as an entire IAA synthesis pathway cluster in SQR9 and B. subtilis 168, all these recombinants showed increased IAA production. These results suggested that gene products of dhaS, patB, yclB, yclC, yhcX and ysnE were involved in IAA biosynthesis. Genes patB, yclC and dhaS constitute a potential complete IPyA pathway of IAA biosynthesis in SQR9. In conclusion, biosynthesis of IAA in B. amyloliquefaciens SQR9 occurs through multiple pathways.